Keragaman Gen Growth Hormone Receptor (GHR) Ekson 10 pada itik Sikumbang Janti - H. Masti; Yurnalis; T. D. Nova; Z. Kamsa; T. Rafian (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
Growth Hormone Receptor (GHR) gene play important roles in duck performances due to their crucialfunctions in growth and has been considered as a candidate gene for growth traits. This reasearch wasaimed to indification polymorphism of Growth Hormon Receptor (GHR) gene in Sikumbang Janti duckand this study used 68 blood duck. Polymerase chain reaction (PCR) and sequencing analysis wereconducted to detect SNP existence in exon 10 of GHR gene. The result of this study showed that wasfound two SNP at g.1112 A>G and g.1304 C>T with transision mutation in exon 10 GHR gene. Genotypesfound in the g.1112 A>G were AA and GG with types of Allele A and G. Genotypes found in the g.1304T>C the were TT and CC with types of Allele T and C. Polymorphism of GHR gene were polymorphicand Population of Sikumbang Janti duck in Hardy-Weinberg equilibrium. It could be concluded thatGHR gene has potential to can be marker genetic in Sikumbang Janti ducks.